Inverse synthetic aperture radar imaging : principles, algorithms, and applications - Chen, Victor C.; Martorella, Marco (Scitech Publishing, an imprint of the IET, 2014)
The following topics are dealt with: ISAR imaging; ISAR motion compensation; ISAR autofocus algorithm; signal processing; ISAR target feature extraction; refocusing moving target; FMCW ISAR; bistatic ISAR; and polarimetric ISAR.
Keywords: Synthetic aperture radar.; Image processing.; elektronické knihy; electronic books